Measured Wave Characteristics in Pearl River Estuary under Typhoon Impact - ZHU Xiaowei; HOU Peng; LIU Xiaojian; WANG Qisong; WANG Qiang; GUO Huiqun; LIU Qinqin (Renmin Zhujiang)
The nearshore wave environment of the Pearl River Estuary is significantly affected by typhoons.Based on the buoy observation data in Macao waters of the Pearl River Estuary,wave characteristic parameters (wave height,wave direction,wave period,etc.) and their correlation during the impact of 11 typhoons from 2017 to 2022 were analyzed,and the impact of typhoons on the nearshore wave environment at the Pearl River Estuary was studied.The results show a high correlation between the maximum wave height and the significant wave height,between the one-tenth of the large waves and the significant wave height,and between the significant wave period and the significant wave height,and then the empirical formula is fitted.During the typhoon influence in this area,the main wave direction is SSE with a frequency of about 37.92%;the secondary wave direction is S with a frequency of about 26.11%.For the extreme waves with a significant wave height of greater than 3 m and a maximum wave height of greater than 4 m,the frequencies are 0.65% and 1.95%,respectively.The wave direction is mainly distributed in ENE-SSW.For long-period waves with a mean wave period of greater than 6 s,the wave direction is mainly distributed in ESE-S,with a frequency of about 12.86%.These wave parameters relationships and characteristics can provide references for the design and research of coastal protection projects such as seawalls and breakwaters in the Pearl River Estuary.